Rhizomatic Protest and Its Impact in Nepal from the Perspective of Gen Z Movement - Adhikari, Dipendra; Gaire, Kushal (NCWA Annual Journal, 2026)
The 2025 Gen Z movement in Nepal cannot be termed as a simplistic youth-driven protest, but it was a structural contest between digitally networked non-state forces and a traditional constitutional state attempting to maintain institutional wholeness. This paper asserts that the separation of powers, legitimization of parties, and small-state digital sovereignty limits were all challenged by rhizomatic, digitally mediated mobilization, which undermined the boundaries of Nepal. This crisis, which saw a former Chief Justice appointed as an interim Prime Minister, sheds some light on the world of how the protests of the digital age can blur constitutional boundaries. In this regard, the Nepali case indicates that youth activism in the platform age is constitutional, political, and geopolitical. The long-held argument is that youth are the most critical actors in social and political change. Nevertheless, the age-based parameters used by international and other regional institutions to define youth are often characterized by the disregard of social, cultural, and political milieus that shape youth agency. Therefore, this article stresses that a contextualized understanding of youth is essential to the critical assessment of the modern protest movements (Pickard, 2020). Since generational mobilization is not only the way to describe the lack of democracies in the country, but also the forces of the large-scale structural transformations in the international order.